The submarine canyons of the Argentine Continental Margin: a review of their formation and sedimentary dynamics (Latin American Journal of Sedimentology and Basin Analysis, 2021)
Submarine canyons are the most outstanding geomorphologic features of continental margins. They play a fundamental role in transferring sedi ment and organic matter from shallow to deep waters. Also, they influence oceanographic and sedimentary processes, interact with productivity and benthic ecosystems, and pose a serious threat to seafloor infrastructures. Submarine canyons have been described as steepwalled, sinuous valleys with Vshaped cross sections, axes sloping outward as continuously as rivercut land canyons and relief comparable to even the largest of land canyons. The understanding of the origin and evolution of submarine canyons has been matter of intense debate since the first geologists observed them characterizing both passive and active margins. Canyons have been interpreted as (1) the offshore prolongation of river systems that during low sea level stages migrated seaward; (2) the product of the erosion caused by gravity dense flows called turbidity currents produced at the shelfslope transition; (3) the deepening of preexisting tectonic structures (e.g. faults) and (4) the result of slope instability combined with headward erosion. The first model only explains the genesis of the breachingshelf canyons that connect with river systems, but does not resolve the formation of those that are unrelated to fluvial input. Turbidity currents take place at the shelf break when sufficient amount of sediment is injected into the water column by (re) suspension, resulting in a flow with higher density than the surrounding waters. These highdensity flows, moving downslope under the effect of gravity, cut the valleys that finally evolve into submarine canyons. Turbidity currents, though effective agents of erosion, do not account for the formation of slope confined canyons. From the other side, tectonic control can apply for limited examples of canyons, which are located in specific geological contexts. Continental slopes often show scars that are left behind by instability events. Mass wasting processes may arise from fluid escape, sediment over pressure and steepening or be triggered by seismic shocks. These initial scars would evolve into rills and then into valleys by a process that combines localized slope failures, sediment funneling and headward erosion. According to this genetic model, slopeconfined and shelfbreaching canyons are, respectively, the early and mature stages in the evolution of canyons, which starts with a precanyon rill that advances upslope by retrogressive failure and ends with the canyon cutting the shelf break. The objective of this contribution is to review the knowledge on the submarine canyons from the Argentine Continental Margin and to suggest a working hypothesis concerning the sedimentary dynamics of the Mar del Plata Canyon, by far the best known canyon of this margin. Four main systems have been described: La Plata River, ColoradoNe gro (or Bahía Blanca), Ameghino (or Chubut) and Patagonia (or Deseado). Mar del Plata Canyon, belonging to the first of these systems, cuts the slope between ~1000 m (Ewing Terrace, middle slope) and ~3900 m (lower slopecontinental rise transition) as a deep valley with steep walls. In its proximal sector, between 1100 and 3000 m, it shows a sinuous path whereas the thalweg is mostly linear between 3000 an 3900 m. Seismic profiles, obtained during the Meteor research cruise M78/3a, demonstrate no evidences of incisions that could suggest past fluvial connections with the canyon head. For this reason, the origin of this canyon has been explained as an example of headward erosion. During the Holocene, the sedimentation rate inside the canyon is much higher than outside. This occurs because the large amount of sediment mobilized by bottom currents along the Ewing Terrace is intercepted by the canyon. In contrast, during the Late Glacial and deglaciation phase, turbidite accumulation has been attributed to slope instability of the drift deposits at the southern flank of the canyon. In this study, we put forward the following working hypothesis: the canyon most probably generated from slope instability and retrogressive erosion. However, when the valley moved upslope and etched the Ewing Terrace (middle slope), turbidity currents might have been produced at this water depth (10001200 meters) by the peculiar oceanographic dynamics driven by the interaction between bottom currents and seafloor. If confirmed by future investigations, this hypothesis would account both for the turbidite deposition and the sinuous path of the canyon in its proximal sector, which is more typical, although not exclusive, for canyons routed by turbidity currents. The detailed morphological investigations, performed in the Patagonia Canyons system by a Spanish research group in 2011, add a stimulating source of discussion about canyon formation in the Argentine Margin. These authors have proposed that topographic irregularities shaped by scars resulting from the seafloor erosion under strong contour currents and the step separating terraces located at different water depths, might be the precursors for a precanyon incision. This hypothesis, of great relevance in a continental margin where down slope and alongslope sedimentary processes often coexist and interact, probably apply not only to the Patagonia but also to the other, less investigated, canyons systems of the Argentine Margin.
Keywords: Argentine Continental Margin, Subma¬rine Canyons, Review, SW Atlantic.